THE EFFECT OF REFERENCE GROUP, ONLINE REVIEW AND PRODUCT RETURN POLICY ON ONLINE PURCHASING DECISIONS - Pratminingsih, Sri Astuti; Pramita, Nadia Cindy; Bahri, Syaiful (CENTRAL ASIA AND THE CAUCASUS, 2022)
The development of the internet plays huge development of e-commerce, Currently, almost all product needs are available through e-commerce. Many factors influence online shopping, one of the factors that can influence the emergence of purchase intentions is the online review of reference group and product return policy, this study aims to determine the influence between the online review reference group and the return policy product on online shopping decisions, research data collection was carried out using incidental sampling type sampling technique with a sample of 105 people. the measurement method uses a Likert scale, statistical data analysis with multiple linear regression analysis, validity and reliability tests, classical assumption tests and hypothesis testing. the results of this study are online review reference groups and product return policies have a positive and significant effect on online shopping decisions.